2018
DOI: 10.1016/j.jnoncrysol.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of shear bands in Zr-Cu metallic glass

Abstract: Shear bands are the key feature that controls deformation in bulk metallic glasses (BMGs). This study provides a comprehensive analysis of plastic deformation of a Zr-Cu-based BMG at room temperature. Experiments were conducted to observe the evolution of shear bands in the material. It was shown that shear bands formed discretely in the material which allows for material deformation to occur across it. Additionally, individual shear bands were characterised to obtain a better understanding of shear-band-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…TEM studies showed that only broad amorphous peaks were present and no indication of crystalinity was found through the presence of Bragg's peaks (see Nekouie et al 2018). As reported by Nekouie et al dark field TEM images also confirmed the absence of crystalline phases in the sample and Selected Area Diffraction (SAED) pattern showed only a set of diffused rings typical for an amorphous structure of glassy nature.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…TEM studies showed that only broad amorphous peaks were present and no indication of crystalinity was found through the presence of Bragg's peaks (see Nekouie et al 2018). As reported by Nekouie et al dark field TEM images also confirmed the absence of crystalline phases in the sample and Selected Area Diffraction (SAED) pattern showed only a set of diffused rings typical for an amorphous structure of glassy nature.…”
Section: Resultssupporting
confidence: 52%
“…Figure 7(c) shows that SBs are not initiated on a plane that lies along the length of the wedge indenter. This was observed in our experiments as on (Nekouie et al 2018). The effect of strain gradients on the initiation and propagation of SBs were studied and the load-displacement curves for different length parameters (l) were compared with the experiment.…”
Section: 2mentioning
confidence: 51%
See 2 more Smart Citations
“…However, the plastic instability of Cu matrix MNCs produced by their shear localization severely disrupts the ability of the material to deform uniformly, limiting its application [5][6][7][8][9]. To effectively control this instability, the process of shear bands (SBs) formation in Cu matrix MNCs needs to be explored.…”
Section: Introductionmentioning
confidence: 99%